Emerging Critical Role of Molecular Testing in Diagnostic Genitourinary Pathology. - Netto, George J.; Cheng, Liang (Archives of Pathology & Laboratory Medicine, 2012)
Context.--The unprecedented advances in cancer genetics and genomics are rapidly affecting clinical management and diagnostics in solid tumor oncology. Molecular diagnostics is now an integral part of routine clinical management in patients with lung, colon, and breast cancer. In sharp contrast, molecular biomarkers have been largely excluded from current management algorithms of urologic malignancies. Objective.--To discuss promising candidate biomarkers that may soon make their transition to the realm of clinical management of genitourologic malignancies. The need for new treatment alternatives that can improve upon the modest outcome so far in patients with several types of urologic cancer is evident. Well-validated prognostic molecular biomarkers that can help clinicians identify patients in need of early aggressive management are lacking. Identifying robust predictive biomarkers that will stratify response to emerging targeted therapeutics is another crucially needed development. A compiled review of salient studies addressing the topic could be helpful in focusing future efforts. Data Sources.--A PubMed (US National Library of Medicine) search for published studies with the following search terms was conducted: molecular, prognostic, targeted therapy, genomics, theranostics and urinary bladder cancer, prostate adenocarcinoma, and renal cell carcinoma. Articles with large cohorts and multivariate analyses were given preference. Conclusions.--Our recent understanding of the complex molecular alterations involved in the development and progression of urologic malignancies is yielding novel diagnostic and prognostic molecular tools and opening the doors for experimental targeted therapies for these prevalent, frequently lethal solid tumors.